O perfil epidemiológico da aids em idosos utilizando sistemas de informações em saúde do datasus: realidades e desafios - Godoy, Vivian S.; Ferreira, Milene D.; Silva, Edilaine Cristina; Gir, Elucir; Canini, Silvia Rita M.S. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: the increase in survival rates associated to changes in elderly sexual behavior, access to drugs for erectile dysfunction and the resistan ce to condom use have given a new epidemiological profile of AIDS in the elderly in recent years. Objective: to identify the epidemiology in AIDS cases diagnosed in Brazil, in individuals aged > 60 years old. Methods: it is an epidemiological study carried out by consulting the DATASUS, the consulted data refers to the period from 1995 to 2005. The collected data was organized and analyzed using the program SPSS 13.0. Results: in this period, 7,955 new cases of AIDS were diagnosed in individuals aged > 60 years, representing 2.42% of the total cases notified in the country. The most frequent category exposition was observed among heterosexuals, most cases are concentrated in the southeast region and the man/woman cases ratio has been changing, in 1995, the ratio was 3:1 and in 2005, 1.5:1. Conclusion: AIDS in the elderly is a reality that imposes many challenges to the health team nowadays. Such as developing and implementing public prevention campaigns aiming specifically at this population, as well as developing a professional practice which to meets the increasing demand of elderly people facing this disease.